Chemical characteristics of Salix psammophila sand barriers are accelerated degradation by ultraviolet irradiation and water - Wang, Ruidong; Meng, Zhongju; Gao, Yong (Frontiers in Plant Science, 2024)
The implementation of Salix psammophila sand barriers measures constitutes a crucial element in desertification control, providing a solid theoretical foundation for the future application and pretreatment of sand barriers in production practices. To address the specific damage types predominant in desert environments, we executed simulations of ultraviolet irradiation and rainfall phenomena on mechanical sand barriers in sandy areas and also inspected the variations in chemical properties during accelerated aging processes. The findings unequivocally demonstrate that: (1) The synergistic impact of ultraviolet irradiation and water accelerated the deformation and fracturing of the S.psammophila sand barriers, thereby causing a partial degradation of its chemical properties and conspicuous lignin oxidation; (2) The fissure of the sand barrier deepened, resulting in structural alterations. The existence of water expedites the degradation process of S.psammophila sand barriers under ultraviolet irradiation. (3)With respect to the binding form of C atoms, the carbon atoms at S.psammophila sand barriers were highly oxidized after 576 hours of accelerated aging. The components of C2 (C-O) and C3 (C=O) rising to 40.16% and 12.24% respectively, while the components of C1 (C-C) declined to 47.60%. The amount of hydroxyl (O-C-O), carbonyl (C=O), and carboxyl (O-C=O) groups increases in line with the expansionof the contact area between the sand barrier structure and ultraviolet irradiation as well as water.. More free radical substances are generated, thereby causing the chemical binding properties to tend to be more stable. In summary, Ultraviolet irradiation and water change are the primary factors influencing the degradation of S.psammophila sand barriers material structure and properties. In future desertification control, it is imperative to focus on enhancing the longevity of sand barriers by ensuring their waterproofing capabilities and resistance to ultraviolet irradiation.